Crystallographic investigationsof urine at newborns with ischemic nephropathy - Loboda A.; Markevych V. (Морфологія, 2012)
The study is devoted to the identification of structural markers of ischemic nephropathy by studying facies (dry drops) of urine in newborn infants. The study involved two groups of full-term newborns with gestational age 38-41 weeks and signs of ischemic nephropathy: 1st - 75 children who suffered severe asphyxia, 2nd - 75 children with moderate asphyxia. Comparison group consisted of 20 infants without asphyxia at birth. Morphological changes were detected in dry drops by microscopy at 40-fold increase in 1-2 and 7-8 days of life. Asphyxia cause disturbance of renal filtration, tubular reabsorption and secretion that lead to increase levels of organic components and mineral salts in urine, crystallization of which forms a specific picture of facies. By urine’s facies morphology at 1-2 days of life is possible to evaluate renal function in newborns suffered from asphyxia. The number of inclusions in facies, their total area and distribution are depending on the severity of asphyxia. Structural changes in the urine of children with ischemic nephropathy remain till the end of the early neonatal period.